Lucio - Arregi, Aitor (Irusion, 2007)
Verzio FF Submission A film about the man who brought to its knees the most powerful bank on the planet by forging traveler’s checks, without missing a single day of work in his construction job. Lucio Urtubia, born in a tiny village in Navarra in North of Spain, has been protagonist and witness to many of the historic events of the second half of the 20th century. His family was persecuted by Franco’s regime, he was on the streets of Paris for the phenomenon of May’68, he actively supported Castro’s revolution, and he helped thousands of exiled people by providing them with false documents. But without a doubt, his greatest triumph came in the second half of the seventies when he managed to swindle the First National Bank (now Citibank) out of 25 million dollars, later investing the money in causes he believed in.